2022
DOI: 10.3390/ijerph19137614
|View full text |Cite
|
Sign up to set email alerts
|

Association of Received Intergenerational Support with Subjective Well-Being among Elderly: The Mediating Role of Optimism and Sex Differences

Abstract: Even though an extensive body of previous research has examined the association between received intergenerational support and the well-being outcomes of older adults in a wide variety of contexts, few studies have been conducted to explore the impacts of intergenerational support on elders’ subjective well-being, especially the intermediary mechanisms in this process. The purpose of this study is to fill this gap by exploring the mediating role of optimism in the association between received intergenerational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…It has been found that the method of directly collecting the data about the respondents' subjective well-being is the most reliable, effective, and comparable [64,65]. Therefore, consistent with previous studies [66,67], subjective well-being was measured by a 5-point Likert-type scale question: "What is your happiness level?" answered ranging from "1 (very unhappy)", "2 (unhappy)", "3 (general)", "4 (happy)", "5 (very happy)".…”
Section: Subjective Well-beingmentioning
confidence: 72%
“…It has been found that the method of directly collecting the data about the respondents' subjective well-being is the most reliable, effective, and comparable [64,65]. Therefore, consistent with previous studies [66,67], subjective well-being was measured by a 5-point Likert-type scale question: "What is your happiness level?" answered ranging from "1 (very unhappy)", "2 (unhappy)", "3 (general)", "4 (happy)", "5 (very happy)".…”
Section: Subjective Well-beingmentioning
confidence: 72%
“…We collected details such as gender, date of birth, marital status, education level, place of residence, health status, number of generations in the family, and the number of sons and daughters. The structured questionnaire on intergenerational support was revised based on the actual situation and has been validated several times in relevant studies involving Chinese populations 7,24–26 …”
Section: Methodsmentioning
confidence: 99%
“…The structured questionnaire on intergenerational support was revised based on the actual situation and has been validated several times in relevant studies involving Chinese populations. 7,[24][25][26] Intergenerational support Intergenerational support is mainly manifested in three aspects: financial support, instrumental support, and emotional support. We used a simple question to evaluate economic support, as to whether their adult children 'Give you money or buy clothes, send food, etc.'…”
Section: Tool For Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations